Ethics in US Government - ROBERTS, Robert North (Greenwood Press, 2001)
From the Abscam investigation to Judge Susan Webber Wright, who presided over the Paula Jones case, this ready-reference encyclopedia provides 264 alphabetically organized entries on the ethics controversies, political scandals, investigations, reforms, and the people involved in them from the formation of the Republic through the year 2000. Throughout American history, political scandals and political reforms have helped to shape the nation's political system. Extensive entries on the activities and players in the Whitewater investigation, Watergate, impeachment proceedings in history, and the ethics controversies in a number of presidential administrations offer full coverage of the most significant ethics controversies in American political history. Entries on legislation, court cases, organizations, and terms and concepts provide needed ready-reference material for student research. More than 65 photographs enliven the text.